CAR T-cells vs. bispecific antibodies as third- or later-line treatment for relapsed/refractory follicular lymphoma: a literature review and meta-analysis - He, Ying; Qiu, Ling; Chen, Dan; Ren, Shi-hui; Xiong, Ya-xin; Li, Meng-jiao; Dou, Bai-tao; Li, Yan-ling; Cen, Ya-li; Li, Yun-ming; Yao, Hao; Fan, Fang-yi (Frontiers in Immunology, 2025)
BackgroundRelapsed/refractory follicular lymphoma (R/R FL) remains a significant challenge in oncology, particularly for patients who have exhausted standard treatment options. Both chimeric antigen receptor (CAR) T-cell therapy and bispecific antibodies(BsAb) have emerged as promising therapeutic modalities in this setting, offering novel mechanisms of action and the potential for improved outcomes. However, comparative data on the efficacy and safety of these treatments remain limited. This study aims to evaluate the clinical outcomes and safety profiles of CAR T-cell therapy versus BsAb as third- or later-line treatments for R/R FL.MethodsA systematic review and meta-analysis were conducted to compare the efficacy and safety of CAR T-cell therapy and BsAb in patients with R/R FL. Studies were selected based on predefined inclusion criteria, and relevant data were extracted to assess overall response rates (ORR), complete remission (CR) rates, progression-free survival (PFS), and the incidence of adverse events, including cytokine release syndrome (CRS) and neurotoxicity. Statistical analyses were performed using random-effects models to account for variability across studies.ResultsThe analysis included 12 studies, with a total of 1,200 patients. CAR T-cell therapy demonstrated superior efficacy compared to BsAb, with a higher ORR (92% vs. 77%)[95% confidence interval (CI) 0.77-0.90] (p= 0.01)and CR rate (82% vs. 65%) [95% CI 0.65-0.80] (p< 0.001). The median PFS was significantly longer for CAR T-cell therapy (15 months) compared to BsAb (9 months). Adverse events were more common in the CAR T-cell group, particularly neurotoxicity (7%[95% CI 0.02-0.13]). However, the overall safety profile was manageable, with most adverse events being grade 1–2 in severity. BsAb were associated with a lower incidence of severe adverse events but showed less favorable efficacy outcomes.ConclusionsOur meta-analysis suggests that CAR T-cell therapy demonstrates a trend toward improved efficacy outcomes compared to bispecific antibodies (BsAb) in R/R FL, with higher response rates and longer PFS. However, this observed advantage must be interpreted cautiously due to potential confounders, including imbalances in baseline tumor burden, prior treatment lines, refractoriness to prior therapy, and variations in bridging therapy protocols across studies. Notably, CAR T-cell therapy was associated with a higher incidence of severe adverse events, particularly neurotoxicity. These findings indicate that while CAR T-cell therapy represents a promising therapeutic strategy, its comparative benefits require validation in studies with matched risk populations and standardized protocols. Future research should prioritize risk-adapted treatment selection and toxicity mitigation strategies for high-risk cohorts.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251107275, Identifier CRD420251107275.